Development and inter-laboratory validation study of an improved new real-time PCR assay with internal control for detection and laboratory diagnosis of African swine fever virus - Tignon, M.; Gallardo, C.; Iscaro, C.; Hutet, E.; Stede, Y. van der; Kolvasov, D.; Mia, G.M. de; Potier, M.F. le; Bishop, Richard P.; Arias, Marisa; Koenen, F. (Elsevier, 2011)
A real-time polymerase chain reaction (PCR) assay for the rapid detection of African swine fever virus (ASFV), multiplexed for simultaneous detection of swine beta-actin as an endogenous control, has been developed and validated by four National Reference Laboratories of the European Union for African swine fever (ASF) including the European Union Reference Laboratory. Primers and a TaqMan probe specific for ASFV were selected from conserved regions of the p72 gene. The limit of detection of the new real-time PCR assay is 5.7 to 57copies of the ASFV genome. High accuracy, reproducibility and robustness of the PCR assay (CV ranging from 0.7 to 5.4%) were demonstrated both within and between laboratories using different real-time PCR equipments. The specificity of virus detection was validated using a panel of 44 isolates collected over many years in various geographical locations in Europe, Africa and America, including recent isolates from the Caucasus region, Sardinia, East and West Africa. Compared to the OIE-prescribed conventional and real-time PCR assays, the sensitivity of the new assay with internal control was improved, as demonstrated by testing 281 field samples collected in recent outbreaks and surveillance areas in Europe and Africa (170 samples) together with samples obtained through experimental infections (111 samples). This is particularly evident in the early days following experimental infection and during the course of the disease in pigs sub-clinically infected with strains of low virulence (from 35 up to 70 dpi). The specificity of the assay was also confirmed on 150 samples from uninfected pigs and wild boar from ASF-free areas. Measured on the total of 431 tested samples, the positive deviation of the new assay reaches 21% or 26% compared to PCR and real-time PCR methods recommended by OIE. This improved and rigorously validated real-time PCR assay with internal control will provide a rapid, sensitive and reliable molecular tool for ASFV detection in pigs in newly-infected areas, control in endemic areas and surveillance in ASF-free areas.